Performance of Low Cost Alternative Radiant Cooling Panel in Malaysia - Imran, Muhammad Syukri; Baharun, Azhaili; Ibrahim, Siti Halipah; Wan Zainal Abidin, Wan Azlan (International Journal of Sustainable Construction Engineering and Technology, 2017)
Radiant panel cooling is still considered uncommon in Malaysia due to unavailability of local manufacturers with limited architects or engineers who are familiar in the system. The initial construction cost for radiant cooling system may be higher than air system and not forgetting the need for a smaller supplementary air system to dehumidify the air to avoid condensation which is an inherited problem of the system in hot and humid region. Promotion and public awareness is lacking in the country and very much dependable on government demonstration program of green technology application where only a few governments owned building having such system. With the aim of long term energy and cost saving this study looks into the development of custom design and locally assembled low cost radiant cooling panel and how its performance in comparison to its overseas and more expensive counterpart could help in provide alternative cheaper building cooling system. Custom build cooling panels with selected materials were constructed and tested to find out its cooling capacity. Finite Element Method (FEM) software was used to establish a design chart to assist in the design and sizing of the alternative radiant panel for Malaysian residential house. The experiment shows that cooling performance in term of mean surface temperature and its cooling capacity is almost identical to its overseas counterpart. Use of cooling radiant panel with free night cooling of water as its chill water supply shows a significant energy saving potential while at the same time provide an acceptable room thermal comfort. Given the local made product having similar performance and suits local condition the technology could grow and be applied with confidence.